Gender Audit for Gender Mainstreaming of Coastal and Marine Fishing Community of India - Asir Ramesh, Devaraj; Bindu, M.V.; Karthi, Nagarathinam (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Fisherwomen constitute 47% of the total adult coastal and marine fishing populations in India. They share major contributions in the fishing of their families either directly or indirectly, especially in post-harvest and land based activities. They have also been involved in passive fishing such as seaweed gathering, mussel collection, and prawn capturing in nearshore coastal ecosystems. The activities performed by fisherwomen in fishing are diverse and different from those of men but significant for the livelihood of their families. Fisherwomen activities amount high in the share of economic contribution to coastal fishing in India. The work performance of fisherwomen in fishing-related activities is un-recognized or under-recognized. Gender biased discrimination such as access to resources, control over family; consumption pattern and freedom for domestic expenditure are prevalent in their family and community. Gender mainstreaming activities of the Government are merely recognized by the fishing community. Gender inequality slows down economic development and deepens poverty in the fishing community. Inadequate recognition of fisherwomen’s contribution in fisheries shall hamper the sustainable development process. Gender equality is a basic of human rights, and its achievement shall bring many long term positive changes in human development and socio-economic progress. A gender audit assesses the extent to which gender equality is effectively institutionalized in the policies, programs, schemes and in the corresponding budgets. To measure the gender gap in coastal fisheries in India, Gender Inequality Index (GII) has been studied. Accordingly, GII in fisheries is 0.618, which is comparatively higher than that of the National average (0.563). This paper discusses the gender gaps in fisheries and requisite gender mainstream activities for fisherwomen empowerment.